Rethinking Perceptions of Crime and Safety in Rural and Remote Communities. (31st May 2022) - David, Jean-Denis
Abstract: This article examines variations in people's perceptions of crime and safety across urban, rural and remote communities, with relative geographical isolation as the defining feature of rurality. Using data from a 2014 representative survey of the Canadian population, our findings suggest that these perceptions are much more nuanced than previously considered. While they tend to be more favourable in rural areas than urban areas, citizen perceptions begin to deteriorate with the relative geographical isolation of communities. In the country's most remote regions, these perceptions are estimated to be even poorer than in urban areas. In sum, rural and remote communities are not the idealized settings so often portrayed in public and academic work.